Fusion of Stacked Nanowires: From Atomistic to Analytical Models. Issue 8 (11th July 2021) - Devaraj, Harish; Jahangir, Md. Naim; Gao, Zhongwei; Chang, Chih‐hung; Malhotra, Rajiv
Abstract: Fusion of metallic nanowires (NWs) is of increasing interest for fabricating printed devices. Atomistic simulations of inter‐NW neck growth during thermal fusion of vertically stacked silver nanowires (NWs) with nonorthogonal axes are performed, a geometric configuration that is commonly seen in applications. High NW rotation during fusion is uncovered surprisingly and found that it accelerates inter‐NW neck growth beyond that explainable by conventional geometric arguments. Rotation‐regulated surface diffusion and dislocation generation are found to be the culpable mechanisms and are shown to be dominant in distinct regimes of initial NW orientation. Motivated by these atomistic observations, an original analytical model of inter‐NW neck growth is formulated and validated. The model accurately predicts the unusual trends in neck growth with six orders of magnitude lesser computational effort than atomistic simulations. Further, it can handle nonisothermal temperature histories over millisecond time scales for NWs up to 100 nm in diameter, a capability that is beyond the reach of typical atomistic simulations. The impact of the revealed spatial disparity of nanoscale neck growth on the properties of random‐packed NW assemblies, and the foundational role of the model in rational design and processing of printed multi‐NW assemblies for a range of applications are discussed. Abstract : An atomistic‐informed analytical model is created for rotation‐driven fusion between stacked nanowires. It captures the unexpectedly nonlinear effect of nanowire orientation, with six orders of magnitude lesser computational effort, and for length and time scales beyond the reach of atomistic simulations. This creates a scalable computational foundation for the rational design of fused nanowire networks in functional devices.